Diseño e implementación de un sistema de monitoreo para un generador eléctrico en el terminal portuario de Guayaquil utilizando el software Labview. - Vivero Bazan, Roberto (2016)
This degree work: "Design and implementation of a monitoring system for an electric generator in the Port Terminal of Guayaquil using the LabView software" uses a SCADA system that monitors an electrical generator. The main reason for the development of this project is to optimize the downtime when power outages occur, whether caused by internal or external personnel of the company. The action of displaying the status of the electrical signals of the company from a remote site is carried out with the purpose of reducing the analysis time and possible trip to the fourth quarter of generators and controls.